Climate Change Awareness and Education: An Antidote to the Impacts of Climate Change - Ajagbe, Charles Adesola (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
Climate change poses a major threat to sustainable development in Nigeria, exacerbating environmental degradation, food insecurity, health challenges, and socio-economic instability. Despite the country’s high vulnerability ranked 160th out of 180 nations awareness and education on climate change remain alarmingly low, with six in ten Nigerians reportedly unaware of the issue. This study conducts a systematic review of peer-reviewed articles, government reports, and grassroots initiatives to examine the role of climate change education (CCE) and public awareness in fostering adaptive and mitigative capacities. Findings reveal research gaps, weak policy implementation, and limited public engagement. Notably, while literature on climate impacts has expanded since 2011, there is an overemphasis on agricultural adaptation at the expense of institutional and cross-sectoral strategies. Misconceptions such as conflating climate change with weather variations or religious beliefs further impede progress. The paper highlights the need to integrate CCE into formal education, strengthen media advocacy, and support youth-led initiatives as pathways to enhance climate resilience in Nigeria.